Cryotherapy in prostate cancer. (September 2014) - Phillips, Jason M; Catarinicchia, Salvatore; Krughoff, Kevin; Barqawi, Al B
Review objectives: Cryotherapy use has increased due to technological advances. A review of the literature was performed to evaluate the efficacy and outcomes of whole gland, salvage and targeted focal cryotherapy in the management of prostate cancer. Review findings: Cryotherapy use has increased significantly over the last 10 years with a trend towards focal ablation. Whole gland cryotherapy, salvage cryotherapy and focal cryotherapy biochemical recurrence rates appear to be comparable to other treatment modalities for low risk disease, however biochemical failure remains difficult to compare across studies due to a lack of consensus regarding appropriate end points for evaluation of cryotherapy. Short-term focal cryotherapy outcomes are encouraging. Side effect profiles for cryotherapy have significantly improved with fourth generation systems while salvage cryotherapy continues to carry a slightly higher risk of incontinence than primary whole gland cryotherapy. The incidence of erectile dysfunction after focal cryotherapy is dramatically lower than that for whole gland ablation. Conclusions: Cryotherapy continues to have an active role in the primary and salvage treatment of prostate cancer. Targeted focal cryotherapy is a promising treatment with minimal morbidity. Further long-term data is needed to support targeted therapy in addition to direct comparison with other treatment modalities.